Extended Endonasal Solo Endoscopic Approach for the Resection of Craniopharyngiomas (Bangladesh Journal of Neuroscience, 2013)
Background: Extended endonasal solo endoscopic approach for the non-pituitary lesions of the sellar and suprasellar regions are not new in the field of neurosurgery. Following endoscopic surgical approach of the pituitary adenoma, endoscopic neurosurgeon is eager to develop the skill for non-pituitary sellar & suprasellar lesions. Common sellar & suprasellar lesions are pituitary adenoma, craniopharyngioma, tuberculumselle meningioma and suprasellar germinoma.Objective: Traditional transsphenoidal approach gives exposure to the pituitary fossa, whereas extended approach provides exposure to the optic nerve, chiasm, acom complex and basal frontal lobe ,mammillary body, mid brain and laterally to the cavernous sinuses.Material & method: From November 2007 to March 2012, 12 cases of done by extended endonasal solo endoscopic approach among 12 cases of craniopharyngiomas. Patient’s history, clinical findings, pre-operative and post-operative visual acuity, visual field and radiological data were collected and analyzed. All patients underwent solo endoscopic extended transsphenoidal approach with or without nasoseptal flap technique for closure. Most of the patients were given lumbar drain as a treatment for CSF leak.Result: All patients were of age group of 10 to 60 years. Male were 8 (66.67%), female were 4 (33.33%) in number. Gross total removals were done in 7 cases out of 12 (58.33%) craniopharyngiomas and subtotal removal done in 5 (41.67%) cases. Visual acuity and field of vision were improved in all cases of craniopharyngiomas. One case (8.33%) of craniopharyngioma had prolong period of unconsciousness probably from hypothalamic disturbance. CSF leak developed in 2 (16.67%) cases. Patients with craniopharyngioma were required thyroxin and cortisol for replacement. Permanent diabetes insipidus developed in 5 cases (41.67%). Three patients required permanent CSF diversion via a ventriculoperitoneal shunt after documentation of postoperative HCP. There was one case of chemical meningitis, and two cases confirmed bacterial infections. Craniopharyngioma can be successfully resected via a purely endoscopic, endonasal approach. Craniopharyngioma have a higher rate of perioperative hydrocephalus and postoperative CSF leak compared with other tumor types in the same area.Conclusion: Extended transsphenoidal approach is an excellent alternative of skull base approach for the removal of most of the craniopharyngioma.The endoscopic endonasal route provides a good exposure, especially of the sub-chiasmatic and retro-chiasmatic areas, as well as of the stalk– infundibulum axis and the third ventricle chamber. It gives better visualization, improved postoperative visual outcome for less manipulation and low complication then craniotomy. However CSF leak and diabetes insipidus is common known complications which have to be manage promptly and appropriately.Bangladesh Journal of Neuroscience 2013; Vol. 29 (2) : 108-114